Affect Theory, Genre, and the Example of Tragedy Dreams We Learn - Lucas, Duncan A. (Palgrave Studies in Affect Theory and Literary Criticism, 2018)
Affect Theory, Genre, and the Example of Tragedy employs Silvan Tomkins' Affect-Script theory of human psychology to explore the largely unacknowledged emotions of disgust and shame in tragedy. The book begins with an overview of Tomkins' relationship to both traditional psychoanalysis and theories of human motivation and emotion, before considering tragedy via case studies of Oedipus, Hamlet, and Death of a Salesman. Aligning Affect-Script theory with literary genre studies, this text explores what motivates fictional characters within the closed conditions of their imagined worlds and how we as an audience relate to and understand fictional characters as motivated humans.